Recent Advances in Multicellular Tumor Spheroid Generation for Drug Screening - Kwang-Ho Lee; Tae-Hyung Kim (Biosensors, 2021)
Multicellular tumor spheroids (MCTs) have been employed in biomedical fields owing to their advantage in designing a three-dimensional (3D) solid tumor model. For controlling multicellular cancer spheroids, mimicking the tumor extracellular matrix (ECM) microenvironment is important to understand cell–cell and cell–matrix interactions. In drug cytotoxicity assessments, MCTs provide better mimicry of conventional solid tumors that can precisely represent anticancer drug candidates’ effects. To generate incubate multicellular spheroids, researchers have developed several 3D multicellular spheroid culture technologies to establish a research background and a platform using tumor modelingvia advanced materials science, and biosensing techniques for drug-screening. In application, drug screening was performed in both invasive and non-invasive manners, according to their impact on the spheroids. Here, we review the trend of 3D spheroid culture technology and culture platforms, and their combination with various biosensing techniques for drug screening in the biomedical field.